Reply to the Comment on 'Klein-Gordon particles in a quasi-pointlike global monopole spacetime and a Wu-Yang magnetic monopole: invariance and isospectrality' - Mustafa, Omar (Iop Publishing Ltd, 2025)
In his Comment the author claims that we have modified the boundary conditions at the origin for the shifted harmonic oscillator and consequently solved a completely different problem in section 7 of J. Phys. G: Nucl. Part. Phys. 51 (2024) 055201. In the current reply, we shall show that the Fernandez claims are incorrect.
Keywords: quasi-pointlike global monopole spacetime; Wu-Yang magnetic monopole; Klein-Gordon particles